Instrumentation for quantitative analysis of volatile compounds emission at elevated temperatures. Part 2: Analysis of carbon fibre reinforced epoxy composite - Lourenço, Cecilia; Bergin, Sarah; Hodgkinson, Jane; Francis, Daniel; Staines, Stephen E.; Saffell, John R.; Walton, Christopher; Tatam, Ralph P. (Nature Publishing Group, 2020)
We have investigated the release of gases and volatile organic compounds (VOCs) from a carbon fibre reinforced epoxy composite matrix used in aircraft structural components. Analysis was performed at several temperatures both up to and above the recommended operating temperature (121 °C) for the material, to a maximum of 250 °C. Gas chromatography-mass spectrometry (GC-MS) combined with thermal desorption (TD-GC-MS) was used to identify and quantify VOCs, and in parallel real-time gas detection with commercial off-the-shelf (COTS) gas sensors. Under hydrocarbon free air, CO, SO2, NO, NO2 and VOCs (mainly aldehydes, ketones and a carboxylic acid) were detected as the gaseous products released during the thermal exposure of the material up to 250 °C, accompanied by increased relative humidity (4%). At temperatures up to 150 °C, gas and volatile emission was limited.